Selection practitioners' views on recruitment criteria for the profile of police officers: A comparison between two police organizations. (June 2016) - Inzunza, Miguel
Abstract: Social changes, associated shifts in police work, and cultural variations raise interesting questions about the ideal police applicant. These issues were explored by investigating key 'suitability' criteria for applicants to join the Swedish National Police and the Catalan Police in Spain. First, criteria and selection procedures in official documents were examined. Next, focus group sessions were carried out with selection practitioners about different criteria. Results indicate several similarities between the organizations in formal criteria and selection procedures, notably an emphasis on peace-making and problem-solving abilities. However, differences were found in areas such as loyalty towards the organization and differences that correspond to different organizational images. The views from the selection practitioners mostly align with the official documents but different outcomes are possible due to different interpretations of how a given construct should manifest itself in actual performance. Practical implications from this study could prove valuable for improving selection practices. Highlights: There are few studies about selection practitioners' views on selection criteria; this study investigates the perspective of two organizations. Several similarities were found between the two organizations operating in culturally different contexts. The findings confirm the complexities previously found in this area and emphasize the importance of using adequate well-defined selection criteria.